Pengembangan Permainan Edufun Number Race Berbasis Ular Tangga untuk Mengembangkan Literasi Numerasi 1-20 pada Anak Usia 5-6 Tahun - Laelatul Musyaroffah; Habib Hambali (Lembaga Yasin AlSys, 2026)
Although play-based learning has received considerable attention in early childhood education research, studies that specifically address the development of integrative numeracy games to support children’s recognition of numbers 1–20 remain limited. This study aimed to evaluate the effectiveness of the Edufun Number Race game in stimulating numeracy literacy among children aged 5–6 years. A quantitative approach was employed using a research and development (R&D) design with the 4D model, involving 94 children selected through purposive sampling. Data were collected using expert validation questionnaires, teacher response questionnaires, observation, and documentation, and were then analyzed using Aiken’s V index and descriptive statistics. The results showed that the medium achieved validity values of ≥ 0.80 and was able to enhance children’s ability to recognize numbers, count, and match numerical symbols. These findings contribute to strengthening constructivist theory and play-based learning approaches, while underscoring the importance of interactive media in numeracy instruction. The study concludes by encouraging educators to integrate educational games into classroom practice as a strategy to stimulate numeracy literacy, with implications for enriching Pendidikan Anak Usia Dini (PAUD) literature and opening avenues for further experiment-based research.